1986
DOI: 10.1111/j.1600-0773.1986.tb02527.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Channel blockers: Spectrum of Side Effects and Drug Interactions

Abstract: Calcium antagonists are a chemically heterogenous group of agents with potent cardiovascular effects which are beneficial in the treatment of angina pectoris, arterial hypertension and cardiac arrhythmias. The main side effects for the group are dose‐dependent and the result of the main action or actions of the calcium antagonists, i.e. vasodilatation, negative inotropic effects and antiarrhythmic effects. Pronounced hypotension is reported for the main calcium antagonist drugs; verapamil, diltiazem and nifedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

1988
1988
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 72 publications
0
6
1
Order By: Relevance
“…We observed more frequent headaches with nifedipine than terbutaline, presumably secondary to nifedipine's vasodilatory effects [36][37][38], a result consistent with previous studies [10,39,40]. Overall, however, previous evidence summaries [2,21,22,31,41] have reported that nifedipine generates fewer total adverse events than terbutaline, a finding that our study confirmed.…”
Section: Discussioncontrasting
confidence: 51%
“…We observed more frequent headaches with nifedipine than terbutaline, presumably secondary to nifedipine's vasodilatory effects [36][37][38], a result consistent with previous studies [10,39,40]. Overall, however, previous evidence summaries [2,21,22,31,41] have reported that nifedipine generates fewer total adverse events than terbutaline, a finding that our study confirmed.…”
Section: Discussioncontrasting
confidence: 51%
“… 10 AML is a third generation dihydropyridine L-type CCB used in the treatment of angina pectoris, arterial hypertension, and cardiac arrhythmias. 11 …”
Section: Introductionmentioning
confidence: 99%
“…This drug has shown a wide range of therapeutic effect, but often it is abandoned due to side effects such as pronounced hypotension, diarrhea, hepatotoxicity, mental confusion, and even death (Hedner 1986; Kloner 1995). It has also been shown to cause gastritis in the GI tract (Lavy 1999).…”
Section: Introductionmentioning
confidence: 99%